2014
DOI: 10.17795/nmsjournal24606
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Hot Pack and Lukewarm-Water-Soaked Gauze on Postoperative Urinary Retention; A Randomized Controlled Clinical Trial

Abstract: Background: Urinary retention is a common postoperative complication that mandates urinary catheterization. Urinary catheterization is associated with different physical, mental, and financial problems for both patients and healthcare systems. The patient inconvenience, urinary tract infections, and increase in hospital stay and expenses are common problems of urinary retention and urinary catheterization. Therefore, alternative ways of relieving urinary retention, preferably noninvasive interventions, are of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…High‐certainty evidence was found for a beneficial effect of applying a hot pack or gauze soaked in warm water to the suprapubic region (OR 0·04, 95 per cent c.i. 0·01 to 0·14; 1 trial). The same trial provided moderate certainty that there was no difference of effect between the two interventions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…High‐certainty evidence was found for a beneficial effect of applying a hot pack or gauze soaked in warm water to the suprapubic region (OR 0·04, 95 per cent c.i. 0·01 to 0·14; 1 trial). The same trial provided moderate certainty that there was no difference of effect between the two interventions.…”
Section: Resultsmentioning
confidence: 98%
“…After removal of duplicate records, 6415 reports were identified of which 48 studies (5644 participants) were included in the review ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reasonable explanation, of how the intervention under the investigation may serve, should be given, especially if there is little or no previous experience with the intervention ( 6 ). Afazel et al ( 5 ) did not present a reasonable explanation for conducting the comparison between a hot pack and lukewarm-water-soaked gauze, on urinary retention.…”
mentioning
confidence: 97%
“…On December 2014, Afazel et al ( 5 ) have reported a clinical trial on comparing the effect of hot pack and lukewarm-water-soaked gauze on postoperative urinary retention. The importance of the issue and conducting a randomized clinical trial are among the strengths of this study, which are supported by an appropriate design.…”
mentioning
confidence: 99%